CircCAPRIN1 interacts with STAT2 to promote tumor progression and lipid synthesis via upregulating ACC1 expression in colorectal cancer. Issue 1 (3rd November 2022) - Yang, Yufei; Luo, Dakui; Shao, Yang; Shan, Zezhi; Liu, Qi; Weng, Junyong; He, Weijing; Zhang, Ruoxin; Li, Qingguo; Wang, Ziliang; Li, Xinxiang
Abstract: Background: Circular RNAs (circRNAs) generated by back‐splicing of precursor mRNAs (pre‐mRNAs) are often aberrantly expressed in cancer cells. Accumulating evidence has revealed that circRNAs play a critical role in the progression of several cancers, including colorectal cancer (CRC). However, the current understandings of the emerging functions of circRNAs in CRC lipid metabolism and the underlying molecular mechanisms are still limited. Here, we aimed to explore the role of circCAPRIN1 in regulating CRC lipid metabolism and tumorigenesis. Methods: circRNA microarray was performed with three pairs of tumor and non‐tumor tissues from CRC patients. The expression of circRNAs were determined by quantitative PCR (qPCR) and in situ hybridization (ISH). The endogenous levels of circRNAs in CRC cells were manipulated by transfection with lentiviruses overexpressing or silencing circRNAs. The regulatory roles of circRNAs in the occurrence of CRC were investigated both in vitro and in vivo using gene expression array, RNA pull‐down/mass spectrometry, RNA immunoprecipitation assay, luciferase reporter assay, chromatin immunoprecipitation analysis, and fluorescence in situ hybridization (FISH). Results: Among circRNAs, circCAPRIN1 was most significantly upregulated in CRC tissue specimens. circCAPRIN1 expression was positively correlated with the clinical stage and unfavorable prognosis of CRC patients. Downregulation of circCAPRIN1 suppressed proliferation, migration, and epithelial‐mesenchymal transition of CRC cells, while circCAPRIN1 overexpression had opposite effects. RNA sequencing and gene ontology analysis indicated that circCAPRIN1 upregulated the expressions of genes involved in CRC lipid metabolism. Moreover, circCAPRIN1 promoted lipid synthesis by enhancing Acetyl‐CoA carboxylase 1 (ACC1) expression. Further mechanistic assays demonstrated that circCAPRIN1 directly bound signal transducer and activator of transcription 2 (STAT2) to activate ACC1 transcription, thus regulating lipid metabolism and facilitating CRC tumorigenesis. Conclusions: These findings revealed the oncogenic role and mechanism of circCAPRIN1 in CRC. circCAPRIN1 interacted with STAT2 to promote CRC tumor progression and lipid synthesis by enhancing the expression of ACC1. circCAPRIN1 may be considered as a novel potential diagnostic and therapeutic target for CRC patients.